PENERAPAN \"PER SE ILLEGAL DAN RULE OF REASON\" DALAM PERKARA OLIGOPOLI INDUSTRI MINYAK GORENG SAWIT DI INDONESIA DENGAN PUTUSAN KPPU NO.24/KPPU-1/2009 TANGGAL 4 MEI 2010 - , Angela Wanodya Sawangi, Drs. Paripurna P. Sugarda, S.H., M.Hum., LL.M ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The spirit of fair trade in market mechanism could be shown through behavior or perfomances of the business entreprenuers. Business actors in trading could perform individually through their corporation or companies or facilitate through trade associations. Indonesia joined the group by enacting of Law No 5/1999 on Prohibitions of Monopolistic Practices and Unfair Business Competition, which regulate business actors in conducting their business. Certainly, it is not easy to change the paradigm or approach from regulated economy to fair business practices towards the market mechanism. There have been several conducts in the past, which were not prohibited but because of the enactment of the new law, considered to be breaching the law. The conducts either known or not known by the business actors or their trade associations constitutes elements, if proved to have anticompetition effect, would be considered breaching the law. Per se illegal is an approach to affirm that such business agreement or activity is illegal without necessarily finding out a further evidence of the business excess. Rule of reason is an approach to evaluate the excess of certain business agreements or activities in order to declare whether or not the business agreements or activities hamper or support to competition. The benefit of using per se illegal method is simplicity and clarity in administrative process, besides it is more powerfull in self-enforcing than prohibitions that depend upon impact evaluation of market complex. Whereas the advantage of rule of reason is to recognize whether or not such businessmen activity has implication on fairness competition through economy analysis. The aim and result of every antimonopoly law, if effective, is in the creation of fair competition in the market economy. Once established, it may generate wealthier public prosperity, improve efficiency amongst economic organizations and therefore enhance national economy competitiveness. To be fair, hopefully, the Court and the Commission (KPPU) together decide the standard of reason whether business arrangement or agreement is restraint of trade or not. These are by no means perfect rules, at least, the Court and/or the Commision has the same perception in the anticipation of the challenger that will be faced with.